Acetic acid induces a programmed cell death process in the food spoilage yeast Zygosaccharomyces bailii - Ludovico, Paula (2003)
Here we show that 320-800 mM acetic acid induces in Zygosaccharomyces bailii a programmed cell death (PCD) process that is inhibited by cycloheximide, is accompanied by structural and biochemical alterations typical of apoptosis, and occurs in cells with preserved mitochondrial and plasma membrane integrity (as revealed by rhodamine 123 (Rh123) and propidium iodide (PI) staining, respectively). Mitochondrial ultrastructural changes, namely decrease of the cristae number, formation of myelinic bodies and swelling were also seen. Exposure to acetic acid above 800 mM resulted in killing by necrosis. The occurrence of an acetic acid-induced active cell death process in Z. bailii reinforces the concept of a physiological role of the PCD in the normal yeast life cycle.